1992
DOI: 10.1007/bf01611175
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen in breast lesions: Correlation of c-erbB-2 oncoprotein and EGF receptor and its clinicopathological significance in breast cancer

Abstract: Monoclonal anti-proliferating cell nuclear antigen (PCNA PC10), which is directed against a 36 kDa auxiliary protein for DNA polymerase delta specific for the S-phase of cell cycle, was used to measure tumour cell proliferation in 4 lactating breasts and 98 benign and malignant breast tumours. The percentage of PCNA-positive cells determined by point counting was significantly lower in the lactating breast [mean 3.6%, standard deviation (SD) 0.67, n = 5] than in fibroadenoma and mastopathy (mean 23.7, SD 5.0, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…In this paper, we demonstrate that all three features are affected by Her2/neu overexpression. Several clinical reports indicate that increased tumor cell proliferation is associated with overexpression of Her2 [13][14][15][16]. Her2 overexpression can also result in increased blood vessel growth as a result of its influence on VEGF expression [18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we demonstrate that all three features are affected by Her2/neu overexpression. Several clinical reports indicate that increased tumor cell proliferation is associated with overexpression of Her2 [13][14][15][16]. Her2 overexpression can also result in increased blood vessel growth as a result of its influence on VEGF expression [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Low vascular density and increased O 2 consumption are affected by Her2/neu expression in tumors. Laboratory studies have shown that Her2 overexpression increases breast tumor cell proliferation which should increase oxygen consumption rates [13][14][15][16]. However, Her2 overexpression can also drive angiogenesis by increasing expression of the proangiogenic cytokine vascular endothelial growth factor (VEGF), independent of hypoxic upregulation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, overexpressions of c-erbB-2 [20,33,34] and p53 [9,15,28] oncoproteins were suggested to be associated with poor prognosis of breast carcinoma. However, other investigations indicate the lack of evidence for prognostic significance of overexpressions of c-erbB-2 [35] and p53 [5,6] oncoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…2,7,25,36,42 Some researchers have noted the value of these nuclear antigens in the prediction of disease-free survival and overall survival as independent prognostic factors in multivariate analyses. 38,41,43 Other authors have reported inconsistent results.…”
mentioning
confidence: 99%